ANALYSIS OF FOOD SECURITY IN SOUTH TANGERANG CITY (THE OBSTACLES OF FOOD SECURITY, AGRICULTURE AND FISHERIES) - Iman S.E. Lubis; Kholidah Tamami; Dien Mardiana Yulianti (Agricultural Socio-Economics Journal, 2020)
The objective of the study is finding the obstacles food security, agriculture and fisheries. This research uses primary data and secondary data such as interview and document literature. Then, we held a focus group discussion to find the real facts. This research uses qualitative research. The schedule of research was between January and July 2019. The result is that the six constraints had been designed but we only found three obstacles which are important for them, i.e. land, capital, institutional and human resources. The main problem of land is limited land; the bulk problem of institution and human resource is the declined young generation to work in farming, and; the problem of capital is that it does not fulfil the needs. Also, in the focus group discussion, the findings of problems are that limited land can be fixed by agreement with Developer, meanwhile capital, institutional and human resources are still dilemmas to be fixed. Further, research will be about irrigation, farmer groups or farmer’s capital in South Tangerang City.